A Comparative Study of 316L Stainless Steel and a Titanium Alloy in an Aggressive Biological Medium - Aroussi, D.; Aour, B.; Bouaziz, A. S. (Engineering, Technology & Applied Science Research, 2019)
The electrochemical behavior of stainless steel and titanium alloys is affected after prolonged contact with basic or acidic solutions, indicating a change in their surface properties. The human body often rejects invasive devices that aim to alter the biological or chemical composition of blood or other body fluids. Stents, fixation plates and screws, spinal implant devices, aneurysm clips, intramedullary nails and stems, temporary fixation devices and surgical instruments, etc. have been made from stainless steel AISI 316L for several years. Although the mechanical performance of implants and devices may be governed by their bulk properties, their interaction with the environment is managed by the characteristics of their superficial layer. In the case of biomedical devices, resistance to corrosion and biocompatibility has paramount importance. This study compares the corrosion behavior of 316L stainless steel and a titanium alloy in a Hank solution. The obtained results show that the titanium alloy has a higher potential than 316L stainless steel and lower corrosion current.